(untitled) (Research, Society and Development, 2022)
Deficiency in sanitary sewage services, mainly in sewage collection and treatment services, results in inadequate sewage disposal in receiving water bodies. This work analyzes the physicochemical and microbiological conditions of Grajaú river for the preponderant bathing conditions established for bathing defined by CONAMA Resolution 274/00. Grajaú, Prainha (P1), Canecão (P2) and Porto do Limoeiro (P3). Physicochemical analyzes of color, chloride, total hardness, alkalinity, pH and microbiological were carried out, through the indicators of the group of total coliforms and (E. coli), using the ALFAKIT methodology in the points. The result was close to 3uH, which allows us to say that the color of the water is within the references required by Conama 357/05. The total alkalinity was 300 mg.L-1 CaCO3, which allows us to conclude that the water of the Grajaú river is hard. The pH in the three samples did not change, it remained 8.0 in the three points, in view of this, these parameters are in accordance with the references of CONAMA n° 274/00. Through this study it was possible to observe that the river waters, based on the indicator, are within the accepted standards for bathing. Still, through this study, it was possible to conclude that it becomes increasingly necessary to monitor the public power facing the Grajaú river, considering that it can be observed that leisure spots are much sought after by the population.